2013
DOI: 10.1021/sc300121j
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Economic and Environmental Assessments of H2O2-based and Tertiary Butyl Hydroperoxide-based Propylene Oxide Technologies

Abstract: Until a decade ago, the industrial technologies for producing propylene oxide from propylene were predominantly based on variations of the venerable chlorohydrin and organic hydroperoxide processes. Within the past decade, highly selective H 2 O 2 -based propylene epoxidation technologies have been developed by Dow-BASF (HPPO process) and the University of Kansas Center for Environmentally Beneficial Catalysis (CEBC-PO process). We present comparative economic and environmental impact analyses based on plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…3 Block diagram describing the various processes included in the cradle-to-gate life-cycle assessment for the production of ethylene from ethanol obtained from corn reported emissions. This trend is similar to what we have reported elsewhere [35][36][37].…”
Section: Validation Of Gabi ò Predictionssupporting
confidence: 93%
“…3 Block diagram describing the various processes included in the cradle-to-gate life-cycle assessment for the production of ethylene from ethanol obtained from corn reported emissions. This trend is similar to what we have reported elsewhere [35][36][37].…”
Section: Validation Of Gabi ò Predictionssupporting
confidence: 93%
“…In several liquid-phase epoxidation routes to convert propene into propene oxide, much attention has been directed to heterogeneous catalytic oxidation using hydrogen peroxide as a more environmentally benign and profitable chemical process [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium silicalite (TS-1) catalyst has been extensively investigated for this route because propene oxide can be produced with a high selectivity in methanol under mild conditions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The direct epoxidation process based on hydrogen peroxide (oxidant) and TS-1 (catalyst) was commercialized and referred to as "hydrogen peroxide-to-propene oxide" (HPPO) process.…”
Section: Introductionmentioning
confidence: 99%
“…The costs associated with utilities and raw materials labor are obtained from specified current sources. Finally, comparative gate-to-gate LCA (life cycle assessment) and cradle-to-gate LCA of both processes are performed to evaluate the relative environmental impacts [127,128].…”
Section: Methodsmentioning
confidence: 99%
“…They found that a subcritical HTW-based process was equally capital intensive, less energy intensive, and more environmentally benign than the current acetic-acidbased process (MC process). [128], all of which were developed by CEBC researchers. The work presented herein is a relatively thorough quantitative evaluation of the CEBC spray technology for TPA production, from both economic and environmental points of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation